Is type 2 diabetes mellitus a vascular disease (atheroscleropathy) with hyperglycemia a late manifestation? The role of NOS, NO, and redox stress. - Melvin R. Hayden; Suresh C. Tyagi (2003)
Cardiovascular disease accounts for at least 85 percent of deaths for those patients with type 2 diabetes mellitus (T2DM). Additionally, 75 percent of these deaths are due to ischemic heart disease.Is type 2 diabetes mellitus a vascular disease (atheroscleropathy) with hyperglycemia a late manifestation? The role of NOS, NO, and redox stress.The vulnerable three arms of the eNOS reaction responsible for the generation of eNO is discussed in relation to the hypothesis: (1) The L-arginine substrate. (2) The eNOS enzyme. (3) The BH4 cofactor.If we view T2DM as a vascular disease initially with a later manifestation of hyperglycemia, we may be able to better understand and modify the multiple toxicities associated with insulin resistance, metabolic syndrome, prediabetes, overt T2DM, and accelerated atherosclerosis (atheroscleropathy). The importance of endothelial nitric oxide synthase, endothelial nitric oxide, tetrahydrobiopterin (BH4), L-arginine, and redox stress are discussed in relation to endothelial cell dysfunction and the development and progression of atheroscleropathy and T2DM. In addition to the standard therapies to restore endothelial cell dysfunction and stabilization of vulnerable atherosclerotic plaques, this article will discuss the importance of folic acid (5MTHF) supplementation in this complex devastating disease process. Atheroscleropathy and hyperglycemia could be early and late manifestations, respectively, in the natural progressive history of T2DM.